1998
DOI: 10.1016/s0092-8674(00)81210-6
|View full text |Cite
|
Sign up to set email alerts
|

Globin Gene Expression Is Reprogrammed in Chimeras Generated by Injecting Adult Hematopoietic Stem Cells into Mouse Blastocysts

Abstract: To elucidate whether the differentiation capacity of hematopoietic stem cells (HSCs) is influenced by specific microenvironments, adult mouse bone marrow-derived HSCs were injected into mouse blastocysts. Embryos developing from injected blastocysts contained donor-derived cells at various developmental stages, and progeny of the stem cells were detected in hematopoietic tissues. Thus, HSCs derived from an adult animal survive after injection into blastocysts and are able to participate in hematopoietic develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 39 publications
5
83
0
2
Order By: Relevance
“…Adult mouse bone marrow-derived HSC have been injected into mouse blastocysts to generate chimeric mice (Geiger et al, 1998). Furthermore, it was shown that the progeny of the adult HSC expressed embryonic/ fetal type globin genes and, conversely, embryonic fetal progenitor cells transplanted to adult mice transcribe the adult-type globin gene.…”
Section: Can Anything Make Anything?mentioning
confidence: 99%
“…Adult mouse bone marrow-derived HSC have been injected into mouse blastocysts to generate chimeric mice (Geiger et al, 1998). Furthermore, it was shown that the progeny of the adult HSC expressed embryonic/ fetal type globin genes and, conversely, embryonic fetal progenitor cells transplanted to adult mice transcribe the adult-type globin gene.…”
Section: Can Anything Make Anything?mentioning
confidence: 99%
“…They also can be reprogrammed to develop into cloned offspring by nuclear transfer (Kawase et al, 2000). Mouse blastocyst is the good microenvironment not only for mouse ES cells or murine hematopoietic stem cells to chimerically redevelop into fetal and adult tissues (Geiger et al, 1998) but also for human hematopoietic stem cells (Harder et al, 2002) and human acute myeloid leukaemia cells (Harder et al, 2003) to redevelop. In the report, murine NS cells contributed to chimeric fetal liver, yolk sac and peripheral blood, but chimeric cells only were detected in adult neural tissues (Harder et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in stem cell research demonstrate that neural stem (NS) cells, which can be isolated from both the fetal and adult central nervous system (Johansson et al, 1999), are not only capable of differentiating into neurones, astrocytes and oligodendrocytes, but also have the potential to differentiate into non-neural progeny in vitro (Galli et al, 2000;Rietze et al, 2001). Some reports also showed that chimeric mice could be produced from adult hematopoietic stem cells (Geiger et al, 1998), as well as adult NS cells (Clarke et al, 2000). These results suggested that NS cells derived from neurospheres had self-renewal capacity and multipotency in the mouse.…”
mentioning
confidence: 99%
“…For example, during fetal development, globin gene expression switches from an embryonic program that takes place in yolk sac blood islands to an adult program when definitive hematopoiesis settles in the fetal liver and later moves to the bone marrow. Surprisingly, injection of adult HSCs into blastocysts yielded embryos that expressed donorderived embryonic globins at the appropriate stages of development and conversely, embryonic and fetal progenitors transplanted into adult recipients were found to express adult type globins (Geiger et al, 1998). These observations suggest that the hematopoietic microenvironment may control the fate of transplanted progenitors, providing further arguments into the stochastic versus inductive debate.…”
Section: Stochastic or Instructive?mentioning
confidence: 96%